An Analysis of Personal Pronoun Errors in Descriptive Text Written by Students of Vocational High School - Livia Luthfiyandini; Syifa Fadhilah Hamid; Marrieta Moddies Swara (Foremost Journal, 2026)
Mastering grammar remains a significant challenge for students, particularly in writing skills. This study investigates students? difficulties in using personal pronouns accurately in writing descriptive texts in English, as incorrect pronoun usage can reduce clarity and coherence in written communication. Although personal pronouns are fundamental components of English grammar, many students still struggle to apply them appropriately in actual writing contexts, indicating a gap between grammatical knowledge and practical use. This research aims to identify the types of personal pronouns used and analyze the errors made by tenth grade students at SMKN 2 Kabupaten Tangerang. A qualitative descriptive method was employed, applying error analysis based on Betty Schrampfer Azar?s (1998) classification of personal pronouns and Dulay, Burt, and Krashen?s (1982) surface strategy taxonomy. Data were collected from 43 students? descriptive texts and analyzed to determine patterns of errors. The findings show that subject pronouns were used most frequently (66%), followed by possessive adjectives (26%) and object pronouns (8%), while possessive and reflexive pronouns were not used. The most dominant error type was misformation, indicating students? difficulty in selecting appropriate pronoun forms based on grammatical function and sentence context. These findings suggest the need for more focused instruction and practice on pronoun usage to improve students? grammatical accuracy in writing.